Perbedaan Lama Pelepasan Tali Pusat Berdasarkan Perawatan Tali Pusat Pada Bayi Baru Lahir - Hariyanto Hariyanto; eva febriana (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2018)
This study aimed at determining the difference in the length of umbilical cord releasebased on umbilical cord care. This research was conducted from February to April 2017.This type of research was an experimental research and the design used was crosssectional. The population in this study were 42 pregnant women estimated to give birth inFebruary-April 2017. The sample of the research was 30 newborns taken with porposivesampling technique. Data collected by observation. Data were analyzed using T Teststatistic test result.The results showed that most, 19 respondents (63,3%) had performed the umbilicalcord care technique correctly. Almost half of respondents, 13 respondents (43,3%) theumbilical cord was release fast. The significant level was 0,000 < 0,50, so it wasconcluded that there was a difference in the length of umbilical cord removal based onumbilical cord care techniques. If the umbilical cord care is correct, it was removed orhealed quickly.Based on the results of the study is expected health workers, especially midwives areencouraged to continue using the correct care of the umbilical cord or sterile gauzebecause it only covers the umbilical cord with sterile gauze, the cord will dry faster andthe cord will release quickly.